Angiotensin ii type 1 receptor gene a1166c polymorphism in hypertension; a study on its influence on aortic stiffness and response to antihypertensive therapy among malays - Rehman, Asia (2005)
Hypertension is a major contributor to cardiovascular disease (CVD) which is the leading cause of death in Malaysia. Aortic stiffness (AS) is an independent marker of cardiovascular (CV) morbidity and mortality in these patients. Angiotensin II type 1 receptor (AT1 R) gene A 1166C polymorphism has been shown to be associated both with essential hypertension and AS measured as pulse wave velocity (PWV). Treatment with angiotensin converting enzyme inhibitor (ACEI) perindopril has been shown to reduce PWV among hypertensive patients carrying C1166 allele. Data on association of AT1 R gene A1166C allele with hypertension among Asians is controversial, while little is known about its association with PWV and its influence on response to antihypertensive treatment. Studies in this thesis were done to determine (1) the association between C1166 poiymorphism of AT1 R gene with hypertension and PWV among Malay hypertensive and normotensive subjects and (2) to study its influence on reduction in PWV comparing two blockers of the renin angiotensin aldosterone system. Two hundred and one hypertensive without evidence of CV complication and 201 age and sex matched normotensive subjects were studied in a cross sectional design. Blood pressure (BP), PWV, anthropometric measurements (height, weight, hip and waist circumference) , were recorded and waist hip ratio and body mass index (BMI) were calculated . Venous blood samples were obtained for routine laboratory investigations and genetic analysis. A 11 66C polymorphism was detected by polymerase chain reaction followed by restriction endonuclease digestion. In a second study 46 hypertensive subjects without C1166 polymorphism of AT1R gene and withouf evidence of target organ damage, were randomly assigned to receive either perindopril or losartan in a double blind parallel fashion for 4 months after a washout period of two weeks. During the study, dose was adjusted to achieve target blood pressure «140/90 mmHg) and if required indapamide 1.5 mg was added to the study medication. Heart rate, systolic and diastolic blood pressure (SSP and DSP) and PWV were measured at the baseline, one month and 4 months after treatment. In both studies PWV was measured using automated Complior® machine. Data from both studies was analyzed using statistical software (SPSS 11.0) using appropriate tests·. Results from study I showed that C1166 allele frequency was 7.96% among hypertensive patients and 7.73% among the normotensive subjects. There was therefore a slightly higher C1166 allele frequency in the hypertensive population which was of borderline Significance (p = 0.091). There was no significant difference in SSP and DSP between carriers and non carriers of C11 66 allele in hypertensive group (p=0.09 and p=0.161, respectively). Likewise there was not significant difference in SBP and DBP in the normotensive group (p=0.708 and p=0.838, respectively) and in the overall study population (p=0.174 and p=0.431, fer SSP and DBP respectively). Subjects carrying (:1166 allele had slightly higher PWV as compared to non carriers in the hypertensive group (11 .09 ± 2.08 vs. 10.72 ± 1.80; p = 0.093) which was also of borderline significance. No difference in PWV was seen among carriers and non carriers in the normotensive group (9.86 ± 1.18 vs. 9.53 ± 1.54, P = 0.440) . However when both normotensives and hypertensives were analyzed together, C 1166 polymorphism carriers had significantly higher PWV as compared to those without this polymorphism (10.52±1 .82 vs. 10.15±1 .80, p= 0.040). In study II, a total of 19 hypertensive patients on losartan and 20 on perindopril completed the study. In both the groups patients had similar age, anthropometric measurements and sex distribution. There was no significant difference in baseline BP (150.89 ± 13.91/93.68 ± 10.37 vs. 151 .85 ± 12.21/91 .65 ± 7.54, P = 0.821 and 0.486) and PWV (11 .63 ± 1.75 vs.10.97 ± 1.69, P =0.293) between the groups. After 4 months treatment there was a significant reduction from baseline in SBP (13.57 ± 15.97, P = 0.002), DBP (8.26 ± 8.54, P = 0.001) and PWV (0.83 ± 1.19, p=0.007) in the losartan group and SBP (17 .95 ± 12.26, P <0.001), DBP (9.25 ± 6.23, P <0.001) and PWV (0.57 ± 1.22, p = 0.047) in the perindopril group. However there was no Significant difference in reduction in SBP (p=0.342), DBP (p = 0.681) and PWV (p = 0.521) between the two groups among Malay hypertensive subjects without C1166 polymorphism. Regression analysis showed that reduction in RWV by losartan and perindopril group was independent of reduction in BP by these drugs and reduction in BP explained about 22 % (~ = 0.221) in losartan group and 21 % (~ = 0.209) in perindopril groups, of the total change in PWV. among Malay hypertensive and normotensive subjects and it is not associated with hypertension. A 11 66C polymorphism is not associated with PWV in hypertensive patients and normotensive subjects but is Significantly associated with PWV in the overall Malay population. Among Malay hypertensive subjects